Data on the Facebook marketing strategies used by fast-food chains in four Latin American countries during the COVID-19 lockdowns - Rozas Urrunaga, Lucila Jimena (2021)
During the COVID-19 pandemic, most countries implemented lockdowns that motivated changes in the dietary patterns, physical activity, and body mass index (BMI) of consumers worldwide, as well as the emergence of new food marketing strategies in social media. We sought to design and validate a methodology for monitoring and evaluating the Facebook marketing strategies of multinational fast-food chains in response to the COVID-19 pandemic.